HIGHER EDUCATION SYSTEM IN MOSCOW AND MOSCOW REGION - Alisa V. Melikyan (Высшее образование в России)
The article presents the results of the study, which aims to quantitatively describe the state of higher education in Moscow and the Moscow region by several characteristics. The article considers quantitative characteristics of the higher education system of these subjects of the Russian Federation, such as the status, specifics of activity, number of students, and departmental affiliation. The location of the higher education institutions in the Moscow region, the distribution of students at institutions of various types and fields of education and the location and the reorganization and liquidation of higher education institutions where analyzed. The study is based on the data of the Monitoring of effectiveness of higher education institutions, which was conducted in 2015. The results ofthe research presented in the article might be of interest to researchers and analysts in the field of education, because it contains analyzed and aggregated quantitative data on certain characteristics of universities and branches located in Moscow and the Moscow region.